Self-efficacy, the relationship with the psychology well-being among private higher education students in Malacca - Wan Othman, Wan Norhayati; Mohamad Yusop, Yusni; Omar, Mohamad Nazli; Yahya, Siti Aishah; Mamat, Suzyliana (Human Resource Management Academic Research Society, 2019)
The purpose of this study was to examine the relationship between the self-efficacy and the psychological well-being of private university student in Melaka. The study was conducted using quantitative method which was a survey in which the questionnaire was distributed to the research samples. The sample of the study was 1500 people among the students of private university in Melaka. The instruments used in this study are the General Self-Efficacy Scale (GSE) and Ryff Psychology Well-being Scale (RPWS). The findings show that there is a positive and significant relationship between the self-efficacy and the psychological well-being of private university student in Melaka. Good Self-efficacy affects the psychological well-being of IPTS students in Melaka.